1997
DOI: 10.1111/j.1439-0507.1997.tb00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and concomitant cutaneous sporotrichosis

Abstract: We report here the case of a 12-year-old girl with concomitant cutaneous and ocular sporotrichosis. Sporothrix schenckii was isolated from skin lesions and aqueous humour. The difficulty in the diagnosis and treatment of this form of mycosis is discussed and the data are compared with those published in the few reports available in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 12 publications
1
28
1
3
Order By: Relevance
“…In immunocompromised individuals, mainly in HIV + patients and alcoholics, the pulmonary and articular forms of sporotrichosis are the most frequent clinical manifestations (5,26). This fungus was also recently isolated from aqueous humor (27). Since this apparent tropism of S. schenckii may be associated with the ability to recognize specific ECM components, we investigated binding of this pathogen to type II collagen.…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompromised individuals, mainly in HIV + patients and alcoholics, the pulmonary and articular forms of sporotrichosis are the most frequent clinical manifestations (5,26). This fungus was also recently isolated from aqueous humor (27). Since this apparent tropism of S. schenckii may be associated with the ability to recognize specific ECM components, we investigated binding of this pathogen to type II collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Until 1990, 17 episodes of endophthalmitis due to S. schenckii had been reported (427). Since then, there have been additional reports of S. schenckii causing endophthalmitis (52,427) and uveitis (410). Vieira-Dias et al (410) reported the occurrence of concomitant ocular and cutaneous sporotrichosis, in which the fungus was isolated from skin lesions and the aqueous humor.…”
Section: Intraocular Mycoses (Excluding Endophthalmitis)mentioning
confidence: 99%
“…Since then, there have been additional reports of S. schenckii causing endophthalmitis (52,427) and uveitis (410). Vieira-Dias et al (410) reported the occurrence of concomitant ocular and cutaneous sporotrichosis, in which the fungus was isolated from skin lesions and the aqueous humor. Risk factors for endophthalmitis due to S. schenckii include AIDS (205) and trauma (427); however, this ocular infection may occur even in the absence trauma or systemic infection (52).…”
Section: Intraocular Mycoses (Excluding Endophthalmitis)mentioning
confidence: 99%
“…Several conditions like alcoholism, diabetes, neoplasia, and acquired immunodeficiency syndrome are associated with disseminated cases and greater severity. [11][12][13] Most human immunodeficiency virus (HIV) -infected patients with disseminated sporotrichosis show protracted conditions, late diagnosis, and poor outcomes, despite antifungal treatment. Meningeal, ocular, respiratory, osteoarticular, and lymphatic involvement have been described as associated with fungemia.…”
Section: Introductionmentioning
confidence: 99%